2009
DOI: 10.1111/j.1600-0668.2008.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of indoor NO2from biomass fuels in rural settings of Ethiopia

Abstract: Respiratory infection is a major cause of morbidity and mortality, globally. Acute respiratory symptoms are also related to high levels of air pollution. Interventions aimed at reducing exposure to indoor air pollution should focus on cooking and heating practices in developing countries. This study is not undermining the role of other biomass smoke constituents in determining respiratory infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 23 publications
3
35
0
Order By: Relevance
“…The levels of benzene and xylene were higher in winter than in summer. Some other studies also found the same seasonal difference [18][19][20]. Ventilation might be a key factor in our study regarding the higher concentrations in winter.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The levels of benzene and xylene were higher in winter than in summer. Some other studies also found the same seasonal difference [18][19][20]. Ventilation might be a key factor in our study regarding the higher concentrations in winter.…”
Section: Discussionsupporting
confidence: 86%
“…Disagreement of our findings with most other studies encouraged us to conduct further study to clarify the seasonal difference as a possible confounding factor in pollution level, as well as the prevalence of symptoms. Some studies have suggested that the level of indoor air pollutants, especially VOCs, were the highest in winter and the lowest in summer [18][19][20]. Thus, we planned to conduct a cross-sectional study in Bangladesh among the biomass-and fossil-fuel users in two different seasons, winter and summer.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the levels of most of indoor air pollutants, especially VOCs, are highest in winter and lowest in summer [14][15][16][17]. The health conditions of the children were then followed between the seasons, i.e., for about 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…Kumie et al [3] found that in one region in Ethiopia the level of NO 2 in households that used biomass fuel for cooking was twice the WHO guideline for NO 2 concentrations. A study in rural southwestern Ethiopian communities [4] documented the biomass fuel-related problems.…”
Section: Introductionmentioning
confidence: 99%